2018
DOI: 10.1093/bioinformatics/bty1011
|View full text |Cite
|
Sign up to set email alerts
|

Insights on protein thermal stability: a graph representation of molecular interactions

Abstract: Motivation Understanding the molecular mechanisms of thermal stability is a challenge in protein biology. Indeed, knowing the temperature at which proteins are stable has important theoretical implications, which are intimately linked with properties of the native fold, and a wide range of potential applications from drug design to the optimization of enzyme activity. Results Here, we present a novel graph-theoretical framewo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 64 publications
0
59
0
Order By: Relevance
“…Miotto et al presented that, molecular interactions in thermal stress-modified protein revealed that the pattern of modification was closely related to the native-fold, energy-related parameters and to the interaction-networks in its structure. This can characterize differentially thermostable proteins 52 . In our current study we have shown a similar pattern of molecular adaptation in different stress-driven (acid, alkali and thermally stable) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Miotto et al presented that, molecular interactions in thermal stress-modified protein revealed that the pattern of modification was closely related to the native-fold, energy-related parameters and to the interaction-networks in its structure. This can characterize differentially thermostable proteins 52 . In our current study we have shown a similar pattern of molecular adaptation in different stress-driven (acid, alkali and thermally stable) proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Complemented with known analysis tools, these techniques have been fruitful in characterizing the dynamic rather than just the static causes of thermostability. MD analysis has been complemented by more global analyses of trajectories, including normal-mode analysis (NMA) [11], principal component analysis (PCA) [12] and residue interaction network (RIN) analysis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, βcoefficient indicates that aromatic amino acids (Trp+Tyr) contributed more to predicting optimal temperature than polar amino acids ( Table 6). Of note, the low prediction value of this model (53%) is because thermostability cannot be solely predicted from the primary sequences of protein 132 .…”
Section: Multiple Regression Analysismentioning
confidence: 94%